A potential framework for cross-zonal reserve procurement on European power exchanges based on robust optimization - Divényi Dániel; Sleisz Ádám; Sőrés Péter Márk; Csercsik Dávid; Hartmann Bálint (SUSTAINABLE ENERGY GRIDS & NETWORKS, 2024)
In order to prepare for unexpected events in the power system, regulation reserves are routinely procured in advance. Economic considerations dictate that it is advantageous to perform reserve procurement and energy allocation on a joint market platform using a single clearing algorithm. Furthermore, it is also beneficial if the option exists to allocate resources between different bidding zones to alleviate local shortages and corresponding price pressures. The present paper proposes a solution algorithm for this task in a European market environment without unit commitment and uplift payments to non-convex bidders. The main challenge of cross-zonal reserve allocation arises from the fact that deployment decisions are not yet known, therefore the actual deployment flows are uncertain at the time of procurement. The proposed algorithm handles this issue with robust optimi- zation techniques and provides a guarantee of feasible transmission limits for deployment i.e. reserve deliver- ability. The clearing model is formalized as a computationally efficient Mixed Integer Linear Problem; its exact equations are presented along with case studies for the purpose of demonstration. The research is part of the FARCROSS H2020 project of the European Union.